Personal Branding Construction in the Formation of Self-Identity of High-Achieving Students - Silvana, Hana; Agustina, Susanti; Saputra, Dimas; Khoerunnisa, Lutfi (Jurnal Riset Komunikasi (JURKOM), 2026)
The development of digital technology has transformed how young people, particularly college students, communicate and develop their identities on social media. Personal branding has become crucial in this era, yet many individuals lack the digital literacy skills necessary to manage it effectively. Low digital literacy can lead to the spread of inaccurate information and inauthentic imagery, which can have negative impacts on digital privacy and reputation. This study aims to understand how high-achieving college students construct their personal brands on social media and the role digital literacy plays in this process. This study employed a descriptive qualitative approach, collecting data through in-depth interviews with six high-achieving college students. The analysis used Miles and Huberman's interactive model. The results revealed that the participants utilized Instagram and LinkedIn in complementary ways: Instagram was used to reach a broader audience through visual narratives, and LinkedIn was used to showcase academic achievements and build professional networks. Interacting with their audience is a crucial strategy for strengthening the credibility of their personal brand, which opens up opportunities for collaboration and professional relationships. Furthermore, digital literacy encompasses not only technical skills but also ethical awareness, critical thinking, and responsibility in managing digital information. In conclusion, high-achieving students' personal branding is formed through the synergy of social media utilization and digital literacy competencies. Together, these serve as a crucial foundation for building academic and professional reputations in the digital age.